2006
DOI: 10.1016/j.jmmm.2005.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Collective states of interacting ferromagnetic nanoparticles

Abstract: Discontinuous magnetic multilayers [CoFe/Al 2 O 3 ] are studied by use of magnetometry, susceptometry and numeric simulations. Soft ferromagnetic Co 80 Fe 20 nanoparticles are embedded in a diamagnetic insulating a-Al 2 O 3 matrix and can be considered as homogeneously magnetized superspins exhibiting randomness of size (viz. moment), position and anisotropy. Lacking intra-particle core-surface ordering, generic freezing processes into collective states rather than individual particle blocking are encountered.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(140 citation statements)
references
References 40 publications
9
129
1
Order By: Relevance
“…But in cases previously reported, the plateau appears at very low fields 17,21,48 and at intermediate fields, the FC curves below T B seem to exhibit a small but monotonic decrease with increasing temperature. 17,18,22 In ANN-7 sample ͑having a SSG behavior͒, a plateau is not observed at intermediate probing fields in the FC curve below the AT line but it appears in the SPM ASD-25 one.…”
Section: Discussionmentioning
confidence: 52%
“…But in cases previously reported, the plateau appears at very low fields 17,21,48 and at intermediate fields, the FC curves below T B seem to exhibit a small but monotonic decrease with increasing temperature. 17,18,22 In ANN-7 sample ͑having a SSG behavior͒, a plateau is not observed at intermediate probing fields in the FC curve below the AT line but it appears in the SPM ASD-25 one.…”
Section: Discussionmentioning
confidence: 52%
“…As a result, χ'' as well as χ' contain only one power law term whose exponent is that of the equilibrium term of TRM experiments. In our experiments, as the frequency range is quite narrow (2.5 orders of magnitude) and the exponents α and Γ are both small, one can fit the measured χ' and χ" by simple power laws with effective exponents α' eff and α" eff : (5) and (6). Considering the uncertainties existing on some of the parameters (e.g.…”
Section: Discussion 4 (A) Consistency Between DC and Ac Resultsmentioning
confidence: 86%
“…Many studies in the past decades ( [6][7][8] and references therein, for a review see [9]) have shown that increasing the nanoparticle concentration in magnetic nanoparticle assemblies yields a transition from a superparamagnetic state to a disordered collective state [10]. This state was called a superspin glass state by analogy with the disordered and frustrated magnetic state observed at low temperatures in spin glass materials [11].…”
Section: Introductionmentioning
confidence: 99%
“…We point out that the dipolar interaction plays a dominant role in granular films when the Co concentration is above a critical concentration as theoretically predicted. 44 However, the positive T 0 's indicate that ferromagneticlike interactions are dominant, which favors the superferromagnetic phase rather than spin-glass phase, as observed by De Toro et al 30 Based on the magnetic phase diagram of a granular system with an insulating matrix proposed by Petracic et al, 45 at sufficiently high concentrations, granular systems with dipolar interactions do not exhibit a superspin glass transition, but a "superferromagnetic transition." It is natural to believe that in the metallic, magnetic granular systems, at a high enough concentration, ferromagneticlike interactions dominate over antiferromagneticlike ones, and thus the condition of competing interactions leading to spin-glass behavior is not fulfilled.…”
Section: ͑4͒mentioning
confidence: 92%